(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
At this stage of the development of linguistics, there is a huge interest in the study of the features of the translation of fiction, the translation of works that belong to the genre of the novel, and scientists are also interested in the analysis of such translations and its practical significance and use on the examples of novels, which is a wide scope for study and research. Since this work is devoted to the study of figurative artistic means in fiction, the subject of the study was a work of fiction written by Margaret Mitchell “Gone with the Wind”. Thus, great attention in this study was paid to the study of the features and analysis of the genre of the novel and its main characteristics and features, since the novel is one of the most popular genres of popular literature.